Sodium-ion batteries: advanced technology and applications - Xie, Man; Wu, Feng (Author of Sodium-ion batteries); Huang, Yongxin (Author of Sodium-ion batteries) (De Gruyter STEM., 2022)
This book provides an in-depth coverage of basic theories, progress and applications of sodium-ion batteries, and introduces the various technologies and mechanisms for anodes, cathodes, and electrolytes. In addition, this book gives insight into industrial applications of sodium-ion batteries.